Magical Thinking in Severe Grief Reactions Theoretical Foundations and New Insights from a Grounded Theory Expert Study - Lönneker, Christian (BestMasters,, 2018)
Christian Lönneker systematically explores the phenomenon of magical thinking in the context of severe grief reactions focusing on intrusive forms reported by bereaved individuals seeking professional support. The author succeeds in proposing a comprehensive definition of magical thinking and a rationale for its association with grief based on various disciplines, such as psychology, anthropology, and the cognitive science of religion. Within the scope of a grounded theory study, case reports comprise themes like bringing the deceased back to life, the magical efficacy of religious rituals, and attempts to ward off harmful influences of the dead. Contents Reactions to Bereavement Bereavement and Psychopathology Perspectives on Magical Thinking Magical Thinking at the Origins of Human Burial Qualitative Methodology in Bereavement Research Themes of Bereavement-Related Magical Thinking Target Groups Lecturers and students of psychology and anthropology Practitioners and researchers in the fields of psychotherapy, grief counseling, palliative and end of life care, funeral directors The Author Christian Lönneker holds a Master of Science in Psychology. Currently, he is preparing for a doctoral program at the Chair of Psychopathology and Clinical Intervention at the Department of Psychology of the University of Zurich, Switzerland, in which he will further investigate magical thinking in severe grief reactions.